Islamic financial literacy, spiritual intelligence, public perception and behaviour on public interest in Islamic banking services - Fitri Yeni; Sitti Rizki Mulyani; Susriyanti Susriyanti (Cogent Economics & Finance, 2023)
This study aimed to determine the effect of Islamic financial literacy, spiritual intelligence, public perception, and behaviour on public interest in Islamic banking services. This research is classified as quantitative research. Islamic financial literacy, spiritual intelligence, and public perception are independent variables. Public behaviour as a mediating variable. The population in this study is the entire community in Padang city who are already customers of Islamic banks. The sample is determined by the Hair method, five times the number of indicators, where the number of indicators is 46 items. The number of respondents in this study was 230 people. Data analysis using structural equation model by using Smart-PLS. The results show Islamic financial literacy and public perception have no significant effect on public interest in Islamic banking services. However, spiritual intelligence has a positive and significant effect on public interest in Islamic banking services. Public behaviour fully mediates the relationship between public perception and public interest in Islamic banking services. Islamic banking is expected to be able to educate prospective customers through increasing spiritual intelligence. Public behaviour can be improved with the religiosity community, thereby increasing interest in saving in Islamic banks.
Keywords: G21; G24; 330; Islamic banking services; Islamic financial literacy; public behaviour; public perception; spiritual intelligence